Cutaneous squamous cell carcinoma metastatic to the axilla and groin: Outcomes and prognostic factors. (9th November 2021) - Bucknell, Nicholas W; Gyorki, David E; Bressel, Mathias; Estall, Vanessa; Webb, Angela; Henderson, Michael; Chua, Margaret S‐T; Rischin, Danny; Tiong, Albert
Abstract: Purpose: This study examined the clinical outcomes and prognostic factors of patients with metastatic cutaneous SCC metastatic to the axilla and groin when managed with curative‐intent lymphadenectomy and received (neo)adjuvant treatment. Methods and Materials: We conducted a single institution retrospective review. Patients who had nodal disease without distant spread were 18 years or older with no non‐cutaneous primary identified. Results: From January 2000 to July 2015, 78 patients were treated for axilla (64, 82%) or inguinal (14, 18%) involvement with cSCC. The median age was 75.5 years (range: 29–95), and 8 patients (11%) were immunosuppressed. The median size of the largest node was 45 mm (range: 8–135), and extracapsular extension was found in 63 (81%) cases. A majority of patients were treated with surgery alone (21, 26.9%) and surgery with adjuvant radiation therapy (54, 69%). The 2‐year OS and PFS were 50% (95% CI: 40%–63%) and 43% (95% CI: 33%–56%), and 5‐year OS and PFS were 33% (95% CI:23%–47%) and 32% (95% CI:22%–46%) respectively in the entire cohort. On univariable analysis, factors associated with longer OS were as follows: younger age (HR 1.1, 95% CI: 0.9–1.3 P  = 0.021), improved performance status (HR 1.5, 95% CI:1.0–2.3 P  = 0.026), lack of immunosuppression (HR 3.3, 95% CI: 1.5–7.3 P  = 0.001), lower lymph node ratio (HR 1.2, 95% CI:1.0–1.3 P  = 0.007), lower number of positive nodes (HR 1.1, 95% CI:1.0–1.2 P  = 0.004) and the use of radiation therapy (HR 0.5, 95% CI:0.3–0.9 P  = 0.012). Conclusion: Metastasis to the axilla and groin with cSCC has poor outcomes with standard treatment. The addition of immunotherapy warrants investigation.